OPTIMASI SUHU ANNEALING UNTUK AMPLIFIKASI GEN AKTIN PADA PANDAN (Pandanus sp) - Larissa Anggisti; Dewi Indriyani Roslim; Herman (UIR Press, 2018)
ABSTRACT Genes expression information involved in Pandanus sp. adaptation in Kajuik Lake sp. to environmental stress is unknown. The genes expression analysis requires the internal control gene such as actin. Actin gene is one of the genes that can be expressed continuously at all stages of plant development. Before obtaining genetic information, it is necessary to isolate and amplify DNA. The purpose of this study was to determine the annealing temperature for actin gene amplification in Pandan (Pandanus sp.). The DNA amplification uses two primer pairs with 20 annealing temperatures. The annealing temperatures were calculated based on the mean values of Tm which were then reduced and added with 5, 4, 3, 2 and 1. The annealing temperature of 53.4 ºC (Tm +1) yielded single thick clear using. The annealing temperature of 53.4 ºC (Tm +1) using P_act_F / P_act_R1 primer pair yielded single, thick and firm DNA band. It was concluded that the annealing temperature for actinin gene amplification in Pandanussp was 53.4 ºC with primer P_act_F / P_act_R1. Keywords: Actin gene, Annealing temperatures, PCR